Biocontrol ability of Bacillus velezensis T9 against Apiospora arundinis causing Apiospora mold on sugarcane - Liao, Jie; Liang, Xuelian; Li, Huiling; Mo, Leixing; Mo, Renfu; Chen, Wei; Wei, Yuning; Wang, Tianshun; Jiang, Wenyan (Frontiers in Microbiology, 2023)
Sugarcane (Saccharum officinarum L.) is susceptible to Apiospora, which can produce the toxin 3-nitropropionic acid (3-NPA) during storage. The consumption of sugarcane that contains 3-NPA can lead to food poisoning. Therefore, this study sought to explore a novel biocontrol agent to prevent and control Apiospora mold. Bacteria were isolated from the soil of healthy sugarcane and identified as Bacillus velezensis T9 through colony morphological, physiological and biochemical characterization and molecular identification. The inhibitory effect of B. velezensis T9 on Apiospora mold on sugarcane was analyzed. Assays of the cell suspension of strain T9 and its cell-free supernatant showed that T9 had significant in vitro antifungal activities against Apiospora arundinis and thus, would be a likely antagonist. Scanning electron microscopy and transmission electron microscopy showed that treatment with T9 significantly distorted the A. arundinis mycelia, perforated the membrane, contracted the vesicles, and decomposed most organelles into irregular fragments. A re-isolation experiment demonstrates the ability of T9 to colonize the sugarcane stems and survive in them. This strain can produce volatile organic compounds (VOCs) that are remarkably strong inhibitors, and it can also form biofilms. Additionally, the cell-free supernatant significantly reduced the ability of A. arundinis to produce 3-NPA and completely inhibited its production at 10%. Therefore, strain T9 is effective at controlling A. arundinis and has the potential for further development as a fungal prevention agent for agricultural products.